Disparities in Pancreatic Ductal Adenocarcinoma—The Significance of Hispanic Ethnicity, Subgroup Analysis, and Treatment Facility on Clinical Outcomes. (13th April 2020) - Riner, Andrea N.; Underwood, Patrick W.; Yang, Kai; Herremans, Kelly M.; Cameron, Miles E.; Chamala, Srikar; Qiu, Peihua; George, Thomas J.; Permuth, Jennifer B.; Merchant, Nipun B.; Trevino, Jose G.
Abstract: Background: Disparities exist among patients with pancreatic ductal adenocarcinoma (PDAC). Non‐White race is regarded as a negative predictor of expected treatment and overall survival. Data suggest that Academic Research Programs (ARP) provide better outcomes for minorities, but ethnic/minority outcomes are underreported. We hypothesize that outcomes among racially/ethnically diverse PDAC patients may be influenced by treatment facility. Methods: The National Cancer Database was used to identify 170, 327 patients diagnosed with PDAC between 2004 and 2015. Cox proportional‐hazard regression was used to compare survival between race/ethnic groups across facilities. Results: In unadjusted models, compared to non‐Hispanic Whites (NHW), non‐Hispanic Blacks (NHB) had the worst overall survival (HR = 1.05, 95%CI: 1.03‐1.06, P  < .001) and Hispanics had the best overall survival (HR = 0.92, 95%CI: 0.90‐0.94, P  < .001). After controlling for socioeconomic and clinical covariates, NHB (HR = 0.95, 95%CI: 0.93‐0.96, P  < .001) had better overall survival compared to NHW, and Hispanics continued to have the best comparative outcomes (HR = 0.84, 95%CI: 0.82‐0.86, P  < .001). Among Hispanics, Dominicans and South/Central Americans lived the longest, at 10.25 and 9.82 months, respectively. The improved survival in Hispanics was most pronounced at ARP (HR = 0.80, 95%CI: 0.77‐0.84, P  < .001) and Integrated Network Cancer Programs (HR = 0.78, 95%CI: 0.73‐0.84, P  < .001). NHB had improved survival over NHW at Comprehensive Community Care Programs (HR = 0.96, 95%CI: 0.93‐0.98, P  = .002) and ARP (HR = 0.96, 95%CI: 0.94‐0.98, P  = .001), which was influenced by income, education, and surgical resection. Conclusion: Survival was improved at ARP for all populations. Hispanics had the best comparative overall survival. NHB had improved overall survival at higher volume centers, but this was dependent upon income, education, and surgical resection. Abstract : Overall survival with pancreatic ductal adenocarcinoma is influenced by where treatment is received, for all races/ethnicities. While racial/ethnic disparities affect overall survival, further subclassification of Hispanics into regions of origin has significant implications in survival and clinical outcomes with pancreatic ductal adenocarcinoma.